RETROSPECTIVE STUDY OF THE IMPACT OF ANTIRETROVIRAL THERAPY ON HIV/AIDS MORTALITY RATES - ABBASI , RI; SHAIKH , JH; GHAFAR , B; ZAREEN, R; ZAFAR , T; KUMAR, A (Biological and Clinical Sciences Research Journal, 2023)
Antiretroviral therapy (ART) has transformed HIV/AIDS from a fatal disease to a manageable chronic condition. The correlation between adherence to ART regimens, immunological and virological markers, and mortality rates among patients with HIV/AIDS necessitates ongoing research. In this retrospective study, we reviewed the medical records of 120 HIV/AIDS patients treated with ART at a tertiary care center. We categorized patients into five ART regimens, assessed reported adherence, and analyzed the corresponding immunological and virological parameters. Furthermore, we evaluated the impact of these factors on mortality rates. The patient distribution was approximately uniform across the five ART regimens. Most patients (60%) demonstrated high adherence to their prescribed regimen. The average CD4 count was 436.83 cells/mm³, and the mean viral load was 73,950 copies/mL. High adherence levels were significantly associated with increased CD4 counts and reduced viral loads. Furthermore, improved immunological and virological outcomes and high adherence levels correlated with decreased mortality rates among the study population. Our study reinforces the importance of adherence to ART regimens in managing HIV/AIDS effectively and reducing associated mortality rates. It underscores the need for individualized regimen selection to optimize patient outcomes and for continued efforts to enhance adherence. Future research should explore strategies to improve adherence and understand the individual variations in response to different ART regimens.